2002
DOI: 10.1073/pnas.122644899
|View full text |Cite
|
Sign up to set email alerts
|

Hemispheric asymmetry in human lateral prefrontal cortex during cognitive set shifting

Abstract: Functional organization of human cerebral hemispheres is asymmetrically specialized, most typically along a verbal͞nonverbal axis. In this event-related functional MRI study, we report another example of the asymmetrical specialization. Set-shifting paradigms derived from the Wisconsin card sorting test were used, where subjects update one behavior to another on the basis of environmental feedback. The cognitive requirements constituting the paradigms were decomposed into two components according to temporal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
103
1
3

Year Published

2002
2002
2008
2008

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 147 publications
(126 citation statements)
references
References 57 publications
19
103
1
3
Order By: Relevance
“…Although it is not clear at this point whether foci 1 and 2 in Figure 4 are separate functional entities, the foci are ϳ2 cm anterior to the posterior frontal regions (near BA 6/44) activated during memory encoding (not significantly activated in this study) (Kelley et al, 1998;Wagner et al, 1998b;McDermott et al, 1999;Konishi et al, 2001). Additionally, the foci are ϳ2 cm dorsal and anterior to focus 3 (Ϫ46, 10, 24), which appears to correspond to the region near BA 45/44 activated during memory retrieval among competitive items (ThompsonSchill et al, 1997) and during inhibitory operations instantiated in classical neuropsychological tasks such as the Stroop task and Wisconsin card sorting task (Taylor et al, 1997;Konishi et al, 2002) (see also Konishi et al, 2001, their Table 2). …”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…Although it is not clear at this point whether foci 1 and 2 in Figure 4 are separate functional entities, the foci are ϳ2 cm anterior to the posterior frontal regions (near BA 6/44) activated during memory encoding (not significantly activated in this study) (Kelley et al, 1998;Wagner et al, 1998b;McDermott et al, 1999;Konishi et al, 2001). Additionally, the foci are ϳ2 cm dorsal and anterior to focus 3 (Ϫ46, 10, 24), which appears to correspond to the region near BA 45/44 activated during memory retrieval among competitive items (ThompsonSchill et al, 1997) and during inhibitory operations instantiated in classical neuropsychological tasks such as the Stroop task and Wisconsin card sorting task (Taylor et al, 1997;Konishi et al, 2002) (see also Konishi et al, 2001, their Table 2). …”
Section: Discussionmentioning
confidence: 46%
“…This region is known to be activated during executive operations for response inhibition instantiated in common neuropsychological tasks such as the Stroop task and the Wisconsin card sorting task (Rushworth et al, 1997;Taylor et al, 1997;Konishi et al, 2002;Nakahara et al, 2002). In the context of memory retrieval, the region is activated during memory retrieval among competitive items (ThompsonSchill et al, 1997), with damage to this region leading to impaired performance of such tasks (Thompson-Schill et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Detailed behavioral analyses in normal human subjects have revealed that inhibition of proactive interference is one of the essential component processes recruited at the time of switching one task to another (9,10). In support of the above findings, neuroimaging studies have demonstrated prominent activation in the lateral prefrontal cortex during set shifting͞task switching (11)(12)(13)(14)(15)(16)(17)(18).…”
mentioning
confidence: 71%
“…A magnet-compatible button press based on a fiber-optic switch was used to record the performance of the subjects. The tasks used in this study were derived from the WCST (20) modified in our previous studies (14,19). In each WCST trial, a five-card display was presented until subjects responded to one of four reference card stimuli at the corner of the screen by matching the attribute of a central card on the basis of the dimension of color, form, or number.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation